PENGARUH PELATIHAN ALTERNATE LEG BOUND DAN SKIPPING TERHADAP KELINCAHAN DAN DAYA LEDAK OTOT TUNGKAI - Gede Eka Pertama, I Putu (Universitas Pendidikan Ganesha, 2013)
This research aimed to determine the affects of alternate leg bound and skipping training to improvement agility and power of leg muscle. This research was a real experiment by the randomizedÂ pre-test post-tes control group design. The research population to 178 and sample are 45 people. Data of agility measured by shuttle run test and power of leg muscle measured by vertical jump test, further data were analyzed with anava one way test and least significant difference (LSD) test at a significance level (Î±) 0.05, by SPSS 16.0. The results showed that an improvement in the average value of the variable agility. Group treatment training alternate leg bound of 2.42, skipping training treatment groups of 1.09 and 0.21 in the control group. On the variable power of leg muscle also improvement the average value. Group treatment alternate leg bound training was 6.26, in the group treated by skipping training 9.13, and 1.53 in the control group. The conclusions training alternate leg bound and skipping is affected to improvement agility and power of leg muscle and there is a difference affected of training alternate leg bound and skipping to improvement agility and power of leg muscle.